Recent Developments in the Endoscopic Treatment of Patients with Peptic Ulcer Bleeding - Jae-Young Jang (Korean Society of Gastrointestinal Endoscopy, 2016)
Peptic ulcer bleeding is an internal medical emergency. Endoscopic hemostasis has been shown to improve the survival rate of patients with peptic ulcer bleeding. Although the established hemostatic modalities, including injection, thermal therapy, and mechanical therapy, are effective in controlling peptic ulcer bleeding, hemostasis can be difficult to achieve in some cases. As a result, recent, new endoscopic hemostatic modalities, including over-the-scope clips, topical hemostatic sprays, and endoscopic ultrasonography-guided angiotherapy, have been developed.